Diagnostic Options and Challenges for Dengue and Chikungunya Viruses. (5th October 2015) - Mardekian, Stacey K.; Roberts, Amity L.
Abstract : Dengue virus (DENV) and Chikungunya virus (CHIKV) are arboviruses that share the same Aedes mosquito vectors and thus overlap in their endemic areas. These two viruses also cause similar clinical presentations, especially in the initial stages of infection, with neither virus possessing any specific distinguishing clinical features. Because the outcomes and management strategies for these two viruses are vastly different, early and accurate diagnosis is imperative. Diagnosis is also important for surveillance, outbreak control, and research related to vaccine and drug development. Available diagnostic tests are aimed at detection of the virus, its antigenic components, or the host immune antibody response. In this review, we describe the recent progress and continued challenges related to the diagnosis of DENV and CHIKV infections.